Peran Dinamika Kelompok dalam Pembentukan Karakter Siswa di SMK Sasmita Jaya 1 Pamulang - Nunung Nurlina; Yunita Fitri Nugraheni; Rini Rendhy; Shinta Widiyanti; Maulidina Ardhianti (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Humans are social creatures who cannot be separated from the existence of the people around them, whether in the family, school, campus, office or in other social life. This writing uses qualitative methods. The results of the research are that character development and character education are a necessity, because education not only makes the nation's children intelligent but also has good character and politeness. Character education involves all aspects of human life, so the emphasis is not only focused on children's cognitive development, but character education in early childhood must be adapted to the child's soul. Schools as institutions that provide services to society by emphasizing social, moral and academic responsibility by integrating character education in all learning material disciplines or in every aspect of the curriculum.